2016
DOI: 10.1002/jhm.2602
|View full text |Cite
|
Sign up to set email alerts
|

The hospitalist perspective on opioid prescribing: A qualitative analysis

Abstract: Background Pain is a frequent symptom among patients in the hospital. Pain management is a key quality indicator for hospitals and hospitalists are encouraged to frequently assess and treat pain. Optimal opioid prescribing, described as safe, patient-centered and informed opioid prescribing, may be at odds with the priorities of current hospital care, which focuses on patient-reported pain control rather than the potential long-term consequences of opioid use. Objective We aimed to understand physicians’ att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 44 publications
4
22
0
Order By: Relevance
“…In line with recent literature, 27,28 we found that our participants reported difficulties balancing PCC and safety for patients with chronic pain, patients on long-term opioid therapy, and patients with an OUD, often labeled as difficult. Labeling a patient as difficult is likely inconsistent with providing PCC and in fact may suggest an interest in avoiding care that fully considers patients' individual values, goals, or preferences.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with recent literature, 27,28 we found that our participants reported difficulties balancing PCC and safety for patients with chronic pain, patients on long-term opioid therapy, and patients with an OUD, often labeled as difficult. Labeling a patient as difficult is likely inconsistent with providing PCC and in fact may suggest an interest in avoiding care that fully considers patients' individual values, goals, or preferences.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are in line with recent literature that shows clinicians use guidelines and state policies to facilitate communication about opioids. 27,28,35 Recent studies 24,34 also highlight clinician concerns over increased regulation of opioid prescribing that may hinder their ability to provide PCC, especially in the area of pain care. On the other hand, such clinician attitudes may be viewed as an attempt to deflect the responsibility for prescribing decisions to something other themselves.…”
Section: Discussionmentioning
confidence: 99%
“…The emotional burden of opioid prescribing and challenging patient conversations are felt across physician specialties. 22,28,29 Opioid prescribing represents a significant proportion of specialist prescribing, with 56% of newly initiated opioid treatments attributed to non-primary care specialties. 30 Although prescriptions are often initiated elsewhere in the system, the prevailing sentiment is that the care of these patients is "dumped" on FPs.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative approach was considered best suited to exploring GP experiences, beliefs and attitudes and their relationship to clinical decision-making 48. A pragmatic integrative approach (ie, both deductive and inductive49) was taken to balance the need for an exploratory approach warranted by the paucity of previous research on problematic use of opioids in the cancer context with the opportunity to build on findings from a large number of studies in the non-cancer pain context 30 31 33 50–62…”
Section: Methodsmentioning
confidence: 99%